Efficacy Of Botanical Pesticides Against Major Pests Of Black Nightshade, Solanum Nigrum Linn - M. SUGANTHY,; P. SAKTHIVEL, (International Journal of Pharma and Bio Sciences, 2012)
Field trials were laid in the farmer’s holdings at Kaalipalayam, Coimbatore district during August, 2011 to November, 2011 to assess the efficacy of selected botanical insecticides against aphids, thrips, leaf miners and defoliators infesting Solanum nigrum. The results of the experiments revealed that among the treatments, foliar spray of profenophos is found to be the best treatment for the management of sucking pests viz., aphids and thrips as well as defoliators viz., leaf miner and other defoliators and also recorded maximum leaf yield. Among the botanicals, 1% azadirachtin and 2 % aqueous extract of Andrographis paniculata recorded maximum reduction in pest population and also conserved more number of natural enemies like predatory coccinellids. Regarding leaf yield, all the botanical pesticides were found to be statistically on par, while the leaf yield recorded from profenophos treated plot recorded its superiority with 21.75 kg leaf /12m2/ harvest.